KEWENANGAN DESK KETENAGAKERJAAN DALAM PENEGAKAN TINDAK PIDANA KETENAGAKERJAAN - Sida Ayu Zahrani; Joko Ismono (Ius Civile: Refleksi Penegakan Hukum dan Keadilan, 2026)
This study analyzes the position and authority of the Indonesian National Police's Manpower Desk in enforcing labor crimes in Indonesia. The background of this study is the rampant violations of workers' normative rights that contain criminal elements, but the enforcement of labor criminal law has not been effective and there is a lack of public knowledge about the authority of the Manpower Desk, the Manpower Inspectorate and the Manpower Office which is in the industrial relations section. The Manpower Desk which was launched in January 2025 is an innovation in the labor law enforcement system that aims to provide protection and legal certainty for workers and business actors. This study uses a normative juridical method by analyzing primary legal materials such as related laws and regulations, in particular, Law No. 8 of 1981 concerning the Criminal Procedure Code, Law No. 13 of 2003 concerning Manpower, Law No. 2 of 2002 concerning the Police, Regulation of the Republic of Indonesia National Police No. 6 of 2019, Law and Law No. 2 of 2004 concerning the Settlement of Industrial Relations Disputes. The legal issue in this study is how the position of the labor desk in the settlement of industrial relations and the differences in authority of the Labor Desk, the Labor Inspector and the Manpower Office. The results of the study indicate that the position of the labor desk is derived from the attribution of authority. The Labor Desk of the Indonesian National Police is positioned as a law enforcement agency that handles labor crimes with the principle of ultimum remedium. The authority of the Labor Desk is an attribute of the Criminal Procedure Code and the Police Regulations including investigations, inquiries, and law enforcement against cases that are indicated as criminal acts, in contrast to the Labor Inspector (PPNS) which functions as primum remedium with a focus on guidance and administrative sanctions, and the Manpower Office which plays a role as a mediator in industrial relations disputes. These three institutions are complementary and need each other in enforcing labor law.